Giant palaeotsunami in Kiribati: Converging evidence from geology and oral history. (19th July 2021) - Terry, James P.; Karoro, Robert; Gienko, Gennady A.; Wieczorek, Marta; Lau, A. Y. Annie
Abstract: For tsunami science within Oceania, the vast Central and Western Pacific (CEWEP) is an anomalous region because of the scarcity of historical tsunami observations and the complete absence of dated palaeotsunami evidence. This paper therefore records the first dated high‐magnitude palaeotsunami event within the CEWEP region. A combination of both geological data and oral history is provided for a palaeotsunami that struck remote Makin island, northernmost of the Gilbert Islands in Kiribati, toward the end of the 16th century. A previously undocumented oral tradition of giant waves is well known to the people of Makin. Narration of this legend by the Wiin te Maneaba, traditional storyteller on Makin, provided important details supporting a tsunami hypothesis. The legend preserves credible information surrounding the giant‐wave origin of Rebua and Tokia, two prominent subaerial megaclasts of blade and block geometry that were transported 80–130 m shorewards from the reef‐edge source and deposited in sideways and inverted orientations. From available hydrodynamic flow transport equations, minimum flow velocities of 7.3–16.3 m s −1 were generated, depending on whether the reefblocks were rotated or lifted onto the reef platform. The youngest U‐Th age‐dates for fossil corals retrieved from the reefblocks give a maximum age for the palaeotsunami of circa AD 1576. Several far‐field Pacific Rim and regional possibilities exist for tsunamigenesis. These include subduction‐zone seismicity and catastrophic volcanic eruption, both of which have been linked to earlier (late 15th century) palaeotsunami events recorded elsewhere in the Pacific Islands. However, the available evidence here suggests that the AD 1576 Makin palaeotsunami was more likely to have been locally generated by tsunamigenic offshore submarine slope failure close to Makin's western reef, associated with the giant arcuate bight structure that characterizes the northern rim of Butaritari atoll.